Secularism and the Question of the "Judeo-Christian" (Relegere: Studies in Religion and Reception, 2012)
This essay comments on the papers in this special issue, paying special attention to "Judaism," "Christianity," and "Judeo-Christian" in relation to discussions of secularism and civil religion. It attempts an explanation of why "Judeo-Christian" has become a term we take for granted, suggesting that the term derives from a tradition of naming and group identity that combines obvious and subtle expressions, habits, and patterns. Finally, it poses questions for further research into the meaning and use of the terms "Judeo-Christian" and "civil religion."